A review of Islamic credit card models in Malaysia - Mohd Noor, Azman; Abdul Aziz, Rafidah (2010)
Islamic credit card or better known as Credit Card-i is one of the alternative banking products introduced by Islamic financial institutions in Malaysia to substitute the conventional credit card. This paper aims at reviewing the structures and instruments applied by Islamic Financial Institutions in Malaysia from Shariah Compliance perspectives. The instruments include tawarruk, inah, and ujrah. The method used is descriptive and positive analytical criticism which aims at improving the existing structure.